User-defined challenges and desiderata for robotics and autonomous systems in health and social care settings. (18th April 2019) - Aguiar Noury, Gabriel; Bradwell, Hannah; Thill, Serge; Jones, Ray
ABSTRACT: We report the needs and challenges identified by health and social care professionals and service users for robotics and autonomous systems that are of importance to researchers and policymakers. To this end, we held eight workshops in different locations across Cornwall (UK) in which we raised awareness of the applications and opportunities of assistive robots. The 223 participants could interact physically with four robots, watched a multimedia presentation including video and use-case scenarios and then took part in 33 focus groups. Content analysis was carried out based on summaries written by facilitators during the focus groups. The focus groups produced 163 challenges that may have digital solutions including 78 suitable for robotic assistive technology, in three main areas: maintaining independence at home, social isolation, and rurality. Although further research is needed with technology and its implementation, this study shows that health and social care professionals, patients, carers, and students are willing to consider using robotics and autonomous systems in health and social care settings. GRAPHICAL ABSTRACT: